Answer:
(f - g)(2) = 2
Step-by-step explanation:
Given the functions below, find (f - g) (2).
f(x) = x² + 3
g(x) = 4x – 3
(f - g)(x) = (x²+3)-(4x-3)
(f - g)(x) = x²+3-4x+3
(f - g)(x) = x²-4x+6
(f - g)(2) = (2)²-4(2)+6
(f - g)(2) = 4-8+6
(f - g)(2) = 2
Answer:
- 0.8
Step-by-step explanation:
The first thing we want to do here is simplify the expression -
( 2x + 5 ) - 2x, Distribute the "
" to elements within the parenthesis
=
2x +
5 - 2x, Focus on simplifying the expression "
2x +
5 "
=
- 2x
=
- 2x, Combine fractions
=
+ 3
=
x + 3
So we have our simplified expression "
x + 3, " with
being the coefficient of x. Our requirements are that this fraction should be expressed as a decimal, so we can simply divide the numerator by the denominator to figure that out,
- 4 / 5 = - 0.8,
Solution = - 0.8
3 consecutive numbers....x, x + 1 and x + 2
x + x + 1 + x + 2 = 72
3x + 3 = 72
3x = 72 - 3
3x = 69
x = 69/3
x = 23
x + 1 = 23 + 1 = 24
x + 2 = 23 + 2 = 25
so ur numbers are 23,24,25 with 25 being the largest
48 divided by 12 = 7
Because 12x7=48
Hope this helped!
Answer: a. True
Step-by-step explanation: